COVID-19 as a Harbinger of Transforming Infrastructure Resilience - Carvalhaes, Thomaz; Markolf, Sam; Helmrich, Alysha; Kim, Yeowon; Li, Rui; Natarajan, Mukunth; Bondank, Emily; Ahmad, Nasir; Chester, Mikhail (Frontiers in Built Environment, 2020)
The COVID-19 pandemic has shocked infrastructure systems in unanticipated ways. Seemingly in the course of weeks, our demands for many basic and critical services have radically shifted. With expected long-term effects (i.e., years), COVID-19 is going to have profound impacts on every facet of infrastructure systems, and will shock these systems very differently than the hazards that we often focus on, such as extreme events, disrepair, and terrorist attacks. At the beginning of this pandemic, infrastructure managers are scrambling to respond to changes in demand, and understand what the long-term effects are for how they operate and maintain their systems. We contend that COVID-19 is revealing several important limitations to how we approach and manage our infrastructure, that must be acknowledged and addressed as the pandemic persists, and in a future increasingly characterized by accelerating and increasingly uncertain conditions. These limitations are how i) we prepare for concurrent hazards, ii) frame criticality based on traditional infrastructure sectors and not human capabilities, iii) we emphasize efficiency at a cost to resilience, and iv) leadership is largely focused on stable conditions. Each of these challenges represents a call for major rethinking for how we approach infrastructure, and COVID-19 presents a window of opportunity for change.